Statistical Yearbook 2021 : In Infographics - Republic of Bulgaria. National Statistical Institute (Republic of Bulgaria: National Statistical Institute, 2022)
The publication is intended for a wider audience as statistical data are presented in a plain and easy understandable way. The current state and changes in the socio-economic and cultural life in the country are presented not in the traditional way in tables and text, but through infographics - images, graphics and other visualization tools.
Basic indicators about the demographic, social and economic development of the Republic of Bulgaria -- Territory, surface area and climate -- Environment -- Population and demographic processes -- Labour market -- Household income, expenditure and consumption -- National accounts -- Prices -- investments --- Finance -- Exports and imports of goods --Energy -- Non-financial enterprises -- Agriculture -- Forestry -- Industry -- Construction -- Transport -- Domestic trade; accommodation and food service activities -- Tourism -- Health -- Education -- Research and development activity and innovation -- Culture and art -- Criminality and justice
Keywords: Bulgaria - Demography; Bulgaria - Statistics; Bulgaria - Socio-economic life; Bulgaria - Cultural life; Republic of Bugaria